Effect of alirocumab on specific lipoprotein non-high-density lipoprotein cholesterol and subfractions as measured by the vertical auto profile method: analysis of 3 randomized trials versus placebo. Issue 1 (December 2016) - Toth, Peter; Hamon, Sara; Jones, Steven; Martin, Seth; Joshi, Parag; Kulkarni, Krishnaji; Banerjee, Poulabi; Hanotin, Corinne; Roth, Eli; McKenney, James
Abstract Background The effect of alirocumab on potentially atherogenic lipoprotein subfractions was assessed in apost ho c analysis using the vertical auto profile (VAP) method. Methods Patients from three Phase II studies with low-density lipoprotein cholesterol (LDL-C) ≥2.59 mmol/L (100 mg/dL) at baseline on stable statin therapy were randomised to receive subcutaneous alirocumab 50–150 mg every 2 weeks (Q2W) or 150–300 mg every 4 weeks (according to study) or placebo for 8–12 weeks. Samples from patients treated with alirocumab 150 mg Q2W (n  = 74; dose common to all three trials) or placebo (n  = 71) were analysed by VAP. Percent change in lipoprotein subfractions with alirocumab vs. placebo was analysed at Weeks 6, 8 or 12 using analysis of covariance. Results Alirocumab significantly reduced LDL-C and the cholesterol content of subfractions LDL1, LDL2 and LDL3+4 . Significant reductions were also observed in triglycerides, apolipoproteins CII and CIII and the cholesterol content of very low-density, intermediate-density, and remnant lipoproteins. Conclusion Alirocumab achieved reductions across a spectrum of atherogenic lipoproteins in patients receiving background statin therapy. Trial registration Clinicaltrials.gov identifiers:NCT01288443, NCT01288469, NCT01266876